2015
DOI: 10.18270/rsb.v4i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional antropométrico de los niños y adolescentes de 17 escuelas del área rural del municipio de La Mesa, Cundinamarca, Colombia, 2012

Abstract: Objetivo. Determinar el estado nutricional de los niños y adolescentes escolares de 17 escuelas del área rural del municipio de La Mesa, Cundinamarca, en 2012.<br />Metodología. Se llevó a cabo un estudio observacional, descriptivo y transversal, en el cual se tomaron medidas antropométricas de peso y talla a 411 niños y adolescentes de 17 escuelas rurales del municipio de La Mesa, en el 2012. Se utilizaron los patrones de crecimiento de la Organización Mundial de la Salud para los niños y adolescentes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Besides, after assessing this phenomenon in the urban area, it was observed that 18.85% and 5.64% of the children had overweight and obese, respectively; meanwhile, in the rural area, the overweight prevalence was 6.31%, and obesity was 0%. Similarly, another study executed by Medina et al 105 aimed to evaluate the nutritional state and BMI of 411 children and teenagers in 17 schools in Cundinamarca's rural area, exhibiting 11.4% had overweight and 1.9% obesity. The rest of the 74.2% of the individuals had average weight (with 11.2% of them at risk of being underweight), and 1.2% had underweight.…”
Section: What Is the Current State Of Colombia?mentioning
confidence: 99%
“…Besides, after assessing this phenomenon in the urban area, it was observed that 18.85% and 5.64% of the children had overweight and obese, respectively; meanwhile, in the rural area, the overweight prevalence was 6.31%, and obesity was 0%. Similarly, another study executed by Medina et al 105 aimed to evaluate the nutritional state and BMI of 411 children and teenagers in 17 schools in Cundinamarca's rural area, exhibiting 11.4% had overweight and 1.9% obesity. The rest of the 74.2% of the individuals had average weight (with 11.2% of them at risk of being underweight), and 1.2% had underweight.…”
Section: What Is the Current State Of Colombia?mentioning
confidence: 99%
“…In the following decades, the literature in this area was fed with information from children and adolescents from different regions of Colombia, mainly from the center of the country: in Aburrá Valley [25], in Medellín [26,27] and other municipalities of Antioquia [28][29][30][31], in Bogotá [32,33], Tunja [34], Pereira [35], other main cities such as Barranquilla and Cali [36] and municipalities such as La Mesa, Cundinamarca [37], and Puerto Colombia, Atlántico [38].…”
Section: Empirical Evidencementioning
confidence: 99%
“…La etapa de la adolescencia es una etapa vulnerable (Isla, Bernal, Pankow, Rivarola, Villalba, & de Arbo, 2015) y decisiva de la vida, ya que tiene directa relación con la adquisición de hábitos, debido a que en este periodo el adolescente va madurando y adoptando los modelos que la sociedad le muestre y que para él resulten atractivos e influyentes (Gutiérrez, Aldea, del Mar Cavia, & Alonso-Torre, 2015). Justamente la adquisición de hábitos poco saludables como la malnutrición, que es una patología dada por el desequilibrio del estado nutricional (Medina, Vargas, Ibáñez & Rodríguez, 2015) y/o sedentarismo, son los que ocasionan problemas de peso, los cuales resultan perjudiciales en esta etapa, ya que, si se tiene sobrepeso u obesidad en la infancia o adolescencia, esto, se asociará fuertemente con sobrepeso u obesidad en la edad adulta, (Ortega et al, 2013) por lo que la actividad física se vuelve fundamental para promover un desarrollo saludable en las etapas de infancia y adolescencia (Oviedo, Sánchez, Castro, Calvo, Sevilla, Iglesias & Guerra, 2013). Asimismo, es importante señalar que esta inactividad física contribuye a un factor de riesgo hacia enfermedades crónicas no transmisibles como en-fermedades cardiovasculares, diabetes tipo II y la misma obesidad (Sánchez, Jardón, Rodríguez & Domínguez, 2014), por lo que su importancia se vuelve aún mayor.…”
Section: Introductionunclassified